Satire Language in Rocky Gerung’s Official Youtube Channel: Critical Discourse Analysis - Sukardi Sukardi; Nurul Wahidah; Annisa Nura’aini (Interference: Journal of Language, Literature, and Linguistics, 2023)
Abstract. This study aims to analyze the diction and satire language style used in critical utterances. The research method used is descriptive qualitative. The theoretical approach used in the analysis in this study is diction and language style, politeness principles and critical discourse analysis. The results of this study reveal that the diction and satire language style used makes the criticism conveyed not rigid, and the message or intent contained therein can be accepted by all viewers. From the point of view of discourse analysis, in terms of the microstructure of the dictions used focus on several lingual features including (1) ideological words that are fought for, (2) ideological meaning relations, (3) euphemistic expressions, (4) striking formal and informal words, (5) metaphors, and (6) positive and negative evaluations. The use of diction and satire language style fulfills the principle of politeness. Therefore, the discourse that is built with satire utterances minimizes conflict and resistance with the interlocutor. Keywords: Critical Discourse Analysis; Diction; Satire Language Style; Principle Of Politeness